CAKUPAN MAKNA MAHKUM ‘ALAIH PADA MUKALLAF DAN BADAN HUKUM DALAM ANATOMI HUKUM ISLAM. - R. Fakhrurrazi; Nihayatut Tasliyah (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
One of the pillars of law (arkanul hukm) in the anatomy of Islamic law is al-Mahkum alaih, namely the party who is charged with carrying out the syara' laws. Thus, those who are obliged to carry out Islamic law, carry out the law, obey the rules are mahkum alaih. Meanwhile, the scope of the meaning of mahkum alaih in classical fiqh is only focused on mukallaf. The concrete meaning of mukallaf as stated in the classical fiqh books, is a Muslim who is mature and has common sense. However, in the development of human civilization, especially in modern times, those who can take legal action and have rights and obligations, not only humans, but "legal entities" can also be in a position like humans in terms of carrying out activities as legal subjects. Experts define a legal entity as an entity that can have assets, rights and obligations like an individual. According to classical fiqh, only humans have rights and obligations and act as legal subjects (mukallaf). Meanwhile, according to modern scientists, those who can become legal subjects or mukallaf, whose actions are recognized by law, and have rights and obligations are not only humans but also legal entities. The difference between these two theories requires academics to immediately conduct research to find out the position of legal entities that can actually act as legal subjects like humans, (such as buying and selling and others) whether they can be included in the legal forum instead of the anatomy of Islamic law or not. no. Then to clarify the direction and object of this research, it will be formulated with the following questions. First, is a legal entity including the meaning of mahkum alaih in the anatomy of Islamic law?. Second, what is the difference between a mukallaf and a non-mukallaf mahkum alaih in the anatomy of Islamic law? The results of this study suggest that there are similarities between the mukallaf and legal entities in terms of being Mahkum alaih in the anatomy of arkanul hukmi. So that a legal entity has the same rights and obligations as a mukallaf person, as well as being able to think about property and assets and other things that can be interpreted by and on behalf of the legal entity itself.